2021
DOI: 10.3390/gels7040239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Resorcinol/Formaldehyde Ratio and the Temperature of the Resorcinol–Formaldehyde Gel Solidification on the Chemical Stability and Sorption Characteristics of Ion-Exchange Resins

Abstract: A series of resorcinol–formaldehyde resins (RFR) samples for Cs-137 removal from liquid alkaline media have been synthesized. It has been demonstrated that the chemical stability as well as sorption characteristics are determined by the resorcinol/formaldehyde molar ratio and the solidification temperature. It has been also demonstrated that the sample synthesized at the resorcinol/formaldehyde molar ratio of 1.8/2.2 and solidified at 210 °C is characterized by the best sorption-selective characteristics and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The crosslinking reactions of PHRO gel are condensation reactions between polyacrylamide (PAM), hexamethylenetetramine (HMTA) and resorcinol (RO). There are three types of crosslinking reactions [ 17 ]: HMTA is hydrolyzed to produce formaldehyde, which is crosslinked with PAM; Formaldehyde reacts with RO to generate polyhydroxy methyl phenol, which is crosslinked with PAM; Formaldehyde reacts with RO to phenolic resin, which is crosslinked with PAM. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crosslinking reactions of PHRO gel are condensation reactions between polyacrylamide (PAM), hexamethylenetetramine (HMTA) and resorcinol (RO). There are three types of crosslinking reactions [ 17 ]: HMTA is hydrolyzed to produce formaldehyde, which is crosslinked with PAM; Formaldehyde reacts with RO to generate polyhydroxy methyl phenol, which is crosslinked with PAM; Formaldehyde reacts with RO to phenolic resin, which is crosslinked with PAM. …”
Section: Resultsmentioning
confidence: 99%
“…The crosslinking reactions of PHRO gel are condensation reactions between polyacrylamide (PAM), hexamethylenetetramine (HMTA) and resorcinol (RO). There are three types of crosslinking reactions [17]:…”
Section: Process Of Crosslinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of the distribution coefficients of Cs-137 in LRW alkaline simulates (NaNO 3 -2.25 mol/L, NaOH-0.75 mol/L) obtained using these materials were above 10 3 mL/g. In addition, we demonstrated earlier that the RFR stability and selectivity to Cs in alkaline solutions can be improved via the optimization of the synthesis parameters [23]. It was shown that the increase of the resorcinol/formaldehyde molar ratio in the reagent mixture from 0.6/2.2 to 1.8/2.2 and the gel solidification temperature from 130 • C to 210 • C yielded a stronger polymer network with an increased accessibility of adsorption sites.…”
Section: Introductionmentioning
confidence: 92%
“…Upon stabilization of the strength code, the current code reflected the strength level of the EHRB, and the corresponding gelation time was documented. Each group had three parallel samples, and the gelation time was the average of the sample data [35,36].…”
Section: Determination Of Gel Time and Gel Strengthmentioning
confidence: 99%